MULTISUBSTITUTED AROMATIC COMPOUNDS AS INHIBITORS OF THROMBIN - DAVID CHARLES WILLIAMS; KEVIN MICHAEL SHORT; SOMALEE DATTA; SON MINH PHAM (2019)
To provide pharmaceutical compositions containing thrombin inhibitors.SOLUTION: The present invention relates to a multisubstituted aromatic compound useful for the inhibition of thrombin, the compound including substituted pyrazolyl or substituted triazolyl. The invention also relates to a pharmaceutical composition containing the compound for treating or preventing thrombotic disorders, such as acute coronary syndrome, venous thromboembolism, arterial thromboembolism, or cardiogenic thromboembolism, or diseases or disorders, such as fibrosis, Alzheimer's disease, multiple sclerosis, pain, or cancer, in a subject in need thereof.SELECTED DRAWING: None 【課題】トロンビン阻害剤を含有する医薬組成物の提供。【解決手段】トロンビンの阻害に有用な、置換ピラゾリルまたは置換トリアゾリルを含む多置換芳香族化合物。急性冠動脈症候群、静脈血栓塞栓症、動脈血栓塞栓症または心原生血栓塞栓症などの血栓性障害、線維症、アルツハイマー病、多発性硬化症、疼痛、がんなどの疾患または障害をその必要のある対象において治療又は予防するための前記化合物を含有する医薬組成物。【選択図】なし